Two lectotypifications and a new combination in Calendula (Asteraceae) for Flora Iberica - Silveira, Paulo Cardoso; Gonçalves, Ana Carla Ramos Da Silva; Santos, Conceição; Paiva, Jorge (Phytotaxa, 2013)
This paper presents a new combination, Calendula suffruticosa subsp. cinerea, and two lectotypifications, for Calendula suffruticosa subsp. tomentosa and Calendula suffruticosa subsp. cinerea, in the course of a taxonomic revision for Flora Iberica. Explanations about the taxonomic concept here adopted are also provided.